Peran Promotional Mix Dalam Membentuk Brand Image Produk City Car di Kota Pekanbaru (Studi Kasus pada Nissan March) - Zaharatul Miladiah; Aida Nursanti; Tengku Firli Musfar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this research is to examine about the use of promotional mix variable which consists of advertising, personal selling, sales promotion, public relations, and direct marketing towards brand image of Nissan March car in Pekanbaru City. Sample’s selection that used with the method of non-probability sampling. Selected sample is only for the consumer that use Nissan March specifically who lives in Pekanbaru city, ever been involved in Nissan March’s promotional mix activity, and the consumer that considered mature enough (about 20 years old) to fill the questionnaire. The data analysis that used is multiple regression linear analysis which use SPSS in version 20. The result indicates simultaneously that all variables of promotional mix have a role in make a brand image of Nissan March car in Pekanbaru City. Known partially that only sales promotion and direct marketing variables that has significant effect for brand image of Nissan March car in Pekanbaru City. Public relation variable also has the role in establish brand image of Nissan March car in Pekanbaru City, however it is not significant. Sales promotion is a kind of promotional mix variable that has the most dominant role in establish brand image of Nissan March car in Pekanbaru City.Keywords: Promotional mix, advertising, personal selling, sales promotion, public relations, direct marketing, and brand image.